Improving the Thermostability and Activity of Transaminase From Aspergillus terreus by Charge-Charge Interaction - Cao, Jia-Ren; Fan, Fang-Fang; Lv, Chang-Jiang; Wang, Hong-Peng; Li, Ye; Hu, Sheng; Zhao, Wei-Rui; Chen, Hai-Bin; Huang, Jun; Mei, Le-He (Frontiers in Chemistry, 2021)
Transaminases that promote the amination of ketones into amines are an emerging class of biocatalyst to prepare a series of drugs or their intermediates. One of the main limitation of (R)-selective amine transaminase from Aspergillus terreus (At-ATA) lies in its weak thermostability, with a half-life (t1/2) of only 6.9 min at 40 °C. To improve its thermostability, four important residue sites (E133, D224, E253, E262) located on the surface of At-ATA were identified via Enzyme Thermal Stability System (ETSS). Subsequently, thirteen mutants (E133A, E133H, E133K, E133R, E133Q, D224A, D224H, D224K, D224R, E253A, E253H, E253K and E262A) were constructed by site-directed mutagenesis according to the principle of turning the residues into opposite charged ones. Among them, three substitutions E133Q, D224K, E253A displayed higher thermal stability than the wild-type enzyme. Molecular dynamics simulations indicated that these three mutations limited the random vibration amplitude in the two α-helix regions of 130-135 and 148-158, thereby increasing the rigidity of the protein. Compared to the wild type, the best mutant D224K showed improved thermostability with a 4.23-fold increase in t1/2 at 40 °C, and with a 6.08 °C increase in T5010 respectively. Exploring three-dimensional structure of D224K at the atomic level, three strong hydrogen bonds were added to form a special “claw structure” of the α-helix 8, and the residues located at 151-156 by interacting with each other alternately also stabilized the α-helix 9.